Quality of life of patients who have undergone the minimally invasive repair of pectus carinatum - BOSTANCI, KORKUT; ERMERAK, NEZİH ONUR (OXFORD UNIV PRESS INC, 2013)
Several studies previously demonstrated an improvement in the quality of life (QoL) of the patients undergoing a minimally invasive repair of pectus excavatum, but there are no data about such improvement following the minimally invasive repair of pectus carinatum (PC) deformity. The purpose of this study was to investigate the effects of the minimally invasive repair of PC deformity on the psychosocial and physical functioning of the patients. Among 40 patients who underwent minimally invasive repair for PC deformity from July 2008 to March 2011, 35 patients accepted to answer the QoL questionnaires, and 30 of them who had completed the postoperative 6th month were evaluated in this study. The modified two-step Nuss questionnaire was used for the QoL assessment. All patients and their parents completed the appropriate questionnaires regarding the patients' preoperative psychosocial and physical functioning, and they were asked to answer the same questions on the postoperative 6th month. The results from these questionnaires were analysed using Wilcoxon signed rank test to investigate the effects of the minimally invasive repair of PC deformity on psychosocial and physical functioning of the patients. The questionnaires used in the study confirmed the positive impact of the surgical correction on psychosocial and physical well-being in the patients and their parents. Spearman's rho correlation coefficient determined how well the answers to the same question at two different times correlated with each other, and Cronbach's alpha demonstrated the internal consistency of these answers. These two parameters showed that the statistical results of the study were reliable enough. Statistical analysis of the scoring of the individual questions and the total scoring of individual patients revealed a statistically significant improvement (P < 0.05) following surgery. Similar significant improvements were observed in the total scoring of individual parents and in most scoring of the individual questions (10 of 13, 77%) in the parental questionnaire (P < 0.05). The results of this study confirm for the first time that minimally invasive repair of PC deformity has a positive impact on both psychosocial and physical functioning of the patient, which is supported by parental assessment.
Keywords: Pectus carinatum; Quality of life; Body image; Nuss questionnaire; CHILD HEALTH QUESTIONNAIRE; SURGICAL REPAIR; NUSS PROCEDURE; BODY-IMAGE; EXCAVATUM; IMPROVES; SURGERY; SELF